Airway stenting in the management of iatrogenic tracheal injuries: 10‐Year experience. Issue 8 (21st July 2016) - Tazi‐Mezalek, Rachid; Musani, Ali I.; Laroumagne, Sophie; Astoul, Philippe J.; D'Journo, Xavier B.; Thomas, Pascal A.; Dutau, Hervé
ABSTRACT: Background and objective: Iatrogenic tracheal injury (ITI) is a rare yet severe complication of endotracheal tube (ETT) placement or tracheostomy. ITI is suspected in patients with clinical and/or radiographic signs or inefficient mechanical ventilation (MV) following these procedures. Bronchoscopy is used to establish a definitive diagnosis. Methods: We conducted a retrospective, single‐centre chart review of 35 patients between 2004 and 2014. Depending on the nature and location of ITI and need for MV, patients were triaged to surgical repair, endoscopic management with airway stents or conservative treatment consisting of ETT or tracheotomy cannula (TC) placement distal to the wound and bronchoscopic surveillance. Results: Three of the four patients (11.43%) presenting with tracheoesophageal fistula (TEF) underwent surgery. Seven patients (20%) who did not require MV underwent endoscopic surveillance. Of the 24 ventilated patients (68.57%), 7 with ITI in the lower trachea were treated with silicone Y‐stent (ETT or TC was placed inside the stent) and 17 patients with ITI in the upper trachea were managed by placing ETT or TC cuff distal to the injury. Overall management success, defined as complete healing of the ITI, was seen in 88.57% of patients. Four patients (11.43%) died of non‐ITI‐related comorbidities. Conclusion: Conservative management should be considered in non‐ventilated patients with ITI and when ITI is located in the upper trachea of ventilated patients where ETT or TC bypasses the injury. Airway stenting should be considered in ventilated patients with ITI located in the lower trachea. Surgery should be reserved for TEF and conservative and endoscopic management failure. Abstract : We describe the role of airway stenting in the delicate treatment of iatrogenic tracheal injuries. Currently, management is guided by case series using different criteria for selecting either conservative or surgical treatment. This is the largest case series ever compiled on this topic. Airway stenting is proposed as a valid treatment option.